2015
DOI: 10.1007/s10457-015-9838-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area

Abstract: Rhizosphere carbon sequestration plays a crucial role in soil carbon dynamics. Little information is available on the dynamics of rhizosphere soil labile organic carbon fractions compared with bulk soil at different citrus stand age. Two replicate sites of three stand ages (10-, 20-, and 30-year) of citrus in the Three Gorges Reservoir area of China were studied. The results showed that rhizosphere soil organic carbon has an increases of 18.76 % under 20-year stand and 11.09 % under 30-year stand compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As an alternative, the rhizobia that do not nodulate their host, along with the vast majority of other resident microbiota, can reasonably expect to survive on the exudates from the plant roots. It has been well-documented that the rhizosphere is far richer in carbon than the surrounding bulk soil (Chiu et al, 2002;Jia et al, 2015). Essentially, all plants release root exudates, and the propensity to seek areas rich in carbon and nitrogen sources would allow rhizobia to acquire nutrients regardless of the source plant.…”
Section: Evidence Against the Possibility Of Flavonoid Chemotaxis In mentioning
confidence: 99%
“…As an alternative, the rhizobia that do not nodulate their host, along with the vast majority of other resident microbiota, can reasonably expect to survive on the exudates from the plant roots. It has been well-documented that the rhizosphere is far richer in carbon than the surrounding bulk soil (Chiu et al, 2002;Jia et al, 2015). Essentially, all plants release root exudates, and the propensity to seek areas rich in carbon and nitrogen sources would allow rhizobia to acquire nutrients regardless of the source plant.…”
Section: Evidence Against the Possibility Of Flavonoid Chemotaxis In mentioning
confidence: 99%
“…The results of some recent studies on the WLFZ showed that the stability of aggregates decreases as hydrological stress increases [18,31,32]. However, studies on the impacts of WLF on the carbon sequestration of different aggregates are still lacking [33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the alternations of SOC in the wetland in the WLFZ is extremely important for the global carbon cycle [34]. However, the background value of SOC is large, and it is difficult to respond quickly to alternations in soil carbon and environment [33]. According to the difficulty of SOC oxidation, Chan et al divided organic carbon into four fractions [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil active organic carbon components are composed of oxidized carbon (ROC) and water-soluble organic carbon (WSOC). ROC is a very abundant active organic carbon component, including easily decomposed humus and polysaccharides (Jia et al, 2015). Humus contains a large number of carboxyl and phenolic hydroxyl acid groups (Bai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%